2013
DOI: 10.1021/ml400014t
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Vitamin D3-Based Hedgehog Pathway Inhibitors That Incorporate an Aromatic A-Ring Isostere

Abstract: Previous structure−activity relationship studies for vitamin D3 (VD3) inhibition of Hedgehog (Hh) signaling directed the design, synthesis, and evaluation of a series of VD3-based analogues that contain an aromatic A-ring mimic. Characterization of these compounds in a series of cellular assays demonstrated their ability to potently and selectively downregulate Hh pathway signaling. The most active of these, 17, inhibited pathway signaling in Hh-dependent mouse fibroblasts (IC 50 = 0.74 ± 0.1 μM) and cultured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Compound 18 exhibited no obvious toxicity up to 100 μ m against astrocytes and gastric epithelial cells GES‐1 ( Figure A ). DAOY cell lines were a suitable human MB model with constitutive Hh activation, which was reported to be resistant to vismodegib in vitro . As illustrated in Figure B , compound 18 decreased proliferation and survival of DAOY cells, although vismodegib was less active.…”
Section: Resultsmentioning
confidence: 99%
“…Compound 18 exhibited no obvious toxicity up to 100 μ m against astrocytes and gastric epithelial cells GES‐1 ( Figure A ). DAOY cell lines were a suitable human MB model with constitutive Hh activation, which was reported to be resistant to vismodegib in vitro . As illustrated in Figure B , compound 18 decreased proliferation and survival of DAOY cells, although vismodegib was less active.…”
Section: Resultsmentioning
confidence: 99%
“…General protocols for cell culture, qPCR, and Hh inhibition in C3H10T1/2 and ASZ001 cells are as previously described . Data were analyzed with GraphPad Prism 5 and reported values represent the mean±SEM for at least two separate experiments carried out in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…[10] Since then, severals eries of VD3 analogues based on this hexahydroindane scaffold were synthesized and evaluated for their Hh inhibitory activity.T he majority of these compounds incorporate an aromaticA -ring mimic linked to the northern region throughavariety of tethers, including esters, amines, or amides. [11][12][13] Severalcompounds with improved anti-Hhactivity have been identified through these studies (Figure 1, 3-6). Our SAR for these analogues clearly demonstrated that ap henyl ring incorporating ah ydrophilic moiety at the meta-o rparaposition is necessary for potent Hh inhibition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these findings, Hadden and co‐workers conducted structural optimizations and further studied their mechanism of action. Among many synthesized analogs, Grundmann's alcohol ( 24 ) (IC 50 = 3.1 μM) was found to be effective against Hh‐dependent C3H10T1/2 cell lines, and showed comparable activity to VD3 (IC 50 = 4.1 μM) against the Hh pathway . Attempts to link an aromatic ring to the structure of compound 24 led to the discovery of representative compounds 25 , 26 , and 27 as potent and selective VD3‐like Hh inhibitors .…”
Section: Hh Signaling Pathway Inhibitorsmentioning
confidence: 99%